Performance testing of a thermoelectric heat pump for centrifugal distillation of wastewater of a space life support system - Anatychuk, L.I.; Rifert, V.G.; Barabash, P.O.; Desiateryk, R.V.; Solomakha, A.S.; Rozver, Yu.Yu.; Petrenko, V.G. (Journal of Thermoelectricity, 2023)
The paper describes the test results of a multistage centrifugal vacuum distillation (CMED) system with a thermoelectric heat pump (THP). The paper presents the results of research on the study of the main characteristics of the process of concentrating water and urine when using three- and five-stage distillers. Particular attention is paid to studying the influence of process parameters on the change in the efficiency of a thermoelectric heat pump. Bibl. 26, Fig. 4, Tabl. 3.